BNAIC 2016 : artificial intelligence : 28th Benelux Conference on Artificial Intelligence, Amsterdam, the Netherlands, November 10-11, 2016, Revised selected papers /: artificial intelligence : 28th Benelux Conference on Artificial Intelligence, Amsterdam, the Netherlands, November 10-11, 2016, Revised selected papers. (2017) - Unknown
No abstract available